Study of the Positive Impact of Using Mathematics Learning Aids on Students - Nurhasanah Nurhasanah; Tika Karlina Rachmawati; Yuli Tri Wiyanto (UIN Sunan Gunung Djati Bandung, 2022)
The aim of this research is to examine the positive impacts that may be present in the use of teaching aids in the students' mathematics learning process. Literature study is the method used in this research. The data collection is done by accommodating information that is in line with the subject being discussed, then the information that has been collected will strengthen the argument from the results of research carried out with a system of reading, citing and managing research materials. The information used comes from journals, scientific articles, and books. All the information cited shows positive results from the data collected and sequentially investigated on the positive impact of teaching aids. The results of this study include: 1. The learning outcomes of students who learn to use teaching aids are superior to those who do not, 2. The learning interest of students who use teaching aids in learning mathematics is more enthusiastic than students who learn to use the usual method, 3. Understanding of students' mathematical concepts those who learn to use teaching aids are higher than students who learn to use the usual method